Modifiable Risk Factors Are Important Predictors of COVID-19-Related Mortality in Patients on Hemodialysis - Kooman, Jeroen Peter; Carioni, Paola; Kovarova, Vratislava; Arkossy, Otto; Winter, Anke; Zhang, Yan; Bellocchio, Francesco; Kotanko, Peter; Zhang, Hanjie; Usvyat, Len; Larkin, John; Stuard, Stefano; et al. (Frontiers in Nephrology, 2022)
Introduction Patients with end-stage kidney disease face a higher risk of severe outcomes from SARS-CoV-2 infection. Moreover, it is not well known to what extent potentially modifiable risk factors contribute to mortality risk. In this historical cohort study, we investigated the incidence and risk factors for 30-day mortality among hemodialysis patients with SARS-CoV-2 infection treated in the European Fresenius Medical Care NephroCare network using conventional and machine learning techniques. Methods We included adult hemodialysis patients with the first documented SARS-CoV-2 infection between February 1, 2020, and March 31, 2021, registered in the clinical database. The index date for the analysis was the first SARS-CoV-2 suspicion date. Patients were followed for up to 30 days until April 30, 2021. Demographics, comorbidities, and various modifiable risk factors, expressed as continuous parameters and as key performance indicators (KPIs), were considered to tap multiple dimensions including hemodynamic control, nutritional state, and mineral metabolism in the 6 months before the index date. We used logistic regression (LR) and XGBoost models to assess risk factors for 30-day mortality. Results We included 9,211 patients (age 65.4 ± 13.7 years, dialysis vintage 4.2 ± 3.7 years) eligible for the study. The 30-day mortality rate was 20.8%. In LR models, several potentially modifiable factors were associated with higher mortality: body mass index (BMI) 30–40 kg/m2 (OR: 1.28, CI: 1.10–1.50), single-pool Kt/V (OR off-target vs on-target: 1.19, CI: 1.02–1.38), overhydration (OR: 1.15, CI: 1.01–1.32), and both low (<2.5 mg/dl) and high (≥5.5 mg/dl) serum phosphate levels (OR: 1.52, CI: 1.07–2.16 and OR: 1.17, CI: 1.01–1.35). On-line hemodiafiltration was protective in the model using KPIs (OR: 0.86, CI: 0.76–0.97). SHapley Additive exPlanations analysis in XGBoost models shows a high influence on prediction for several modifiable factors as well, including inflammatory parameters, high BMI, and fluid overload. In both LR and XGBoost models, age, gender, and comorbidities were strongly associated with mortality. Conclusion Both conventional and machine learning techniques showed that KPIs and modifiable risk factors in different dimensions ascertained 6 months before the COVID-19 suspicion date were associated with 30-day COVID-19-related mortality. Our results suggest that adequate dialysis and achieving KPI targets remain of major importance during the COVID-19 pandemic as well.